Jenis, Potensi dan Nilai Ekonomi Hasil Hutan yang Dimanfaatkan Masyarakat sekitar Tahura Bukit Barisan - Faujiah Nurhasanah; Ridwanti Batubara; Oding Affandi (Peronema Forestry Science Journal, 2012)
TAHURA Bukit Barisan represent a forest bunch which is have direct interaction between people and forest. Doulu and Jaranguda Village is around Tahura area. Therefore was conducted   research to know type, potency  and economic value of forest product which  exploited  by society around TAHURA. The method that is used to determine  the respondent is snowball sampling method. Based on interview on  responden, type of forest  product which  exploited by  people around TAHURA area are  regen bamboo, bulak bamboo, medical plant, honey and animal . The biggest Economics value at both village  is Bamboo Regen exploiting equal to Rp.1.069.256.000,00. Forest provide a major contribution to public life. Key words : TAHURA, type, economic value, contribution